Modeling and optimization of PV-diesel-biogas hybrid microgrid energy system for sustainability of electricity in Rural Area - Timothy Oluwaseun Araoye; Evans Chinemezu Ashigwuike; Sadiq Abubakar Umar; Emmanuel M. Eronu; Thank God Izuchukwu Ozue; Sochima Vincent Egoigwe; Muncho Josephine Mbunwe; Matthew Chinedu Odo Odo; Nnaemeka Genesis Ajah (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The paper presented a hybrid micro-grid renewable energy of different energy sources to generate uninterrupted electricity for the Agu-Amede village using PV, diesel, biogas, and battery. The system optimization was performed to determine techno-economic analysis and energy generated using HOMER software. The energy generated by the hybrid system was able to meet the demand load of the village at all levels of biomass production with surplus electricity in each case when the production of the biogas system varied between 0.5 tons to 3 tons. At biomass production of 3 tons, the total energy generated demand is 480693 kWh with a surplus of 121762 kWh. Again, the hybrid PV and biogas system generate total energy of 98714 kWh (20.50%) and 381979 kWh (79.50%), respectively. The net present cost (NPC) and cost of energy (COE) of the base case architecture (diesel) measured are $1230000 and $0.267/kWh, respectively. Therefore, between 2.5 tons and 3.0 tons of biomass penetration, the energy production of biogas increased, and the diesel system was removed from the hybrid system setup. This is because the availability of biogas is almost sufficient to meet the load demand at a lower cost and solar PV architecture was added to the hybrid system to balance energy production.